THE IMPACT OF THE IMPULSE BUYING DIMENSION AND CHERRY PICKING: AN EMPIRICAL STUDY (Consumers Case Study in a mall in Central Jakarta) - Endang Ruswanti (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
The purpose of this research is to further test the contradictory research result. Mathai & Haridas’ findings (2014) stated that a discounted price did not influence impulse buying. Meanwhile Ruswanti, (2013) found that a discounted price tended to influence the consumers’ spontaneous shopping. Data discovered by Nielsen (2007) stated that apparently 85% of Indonesian consumers tend to buy things on an impulse. This research was in the form of a survey, the sample being 197 people, of whom 96 respondents were female, and males the other 101. The respondents ages were between 17-50 years old, those with an income of 3 million rupiahs numbered 83 persons, 64 people had an income above 5 millions rupiahs, and 50 respondents had an income above 10 million rupiahs. The technical design was a purposive sampling;70% of the consumers liked the discounted products, and bought something on the spur of the moment at least once. The regression analysis was with SPSS 19; the results show that the external, internal, situational environment, products’ variety, and sociocultural effects significantly influenced the cherry picking. The respondents with an income of above 3-5 million preferred spontaneous shopping. This research gives a contribution to the development of the consumers’ behavioral theory through impulse buying and cherry picking.Keyword: Impulsive Buying Dimension, Cherry Pick, Consumer’s Behavioral, Central Jakarta